Musculoskeletal Injuries among Hospital Patient Care Staff before and after Implementation of Patient Lift and Transfer Equipment - Schoenfisch, Ashley L; Lipscomb, Hester J; Pompeii, Lisa A; Myers, Douglas J; Dement, John M (Scandinavian Journal of Work, Environment ＆ Health, 2013)
Objective Using an observational research design and robust surveillance data, we evaluated rates of musculoskeletal (MS) injuries, days away from work, and restricted work days among patient care staff at a medical center and community hospital in the United States over 13 years, during which time a "minimal manual lift" policy and mechanical lift equipment were implemented. Methods Workers' compensation claims data were linked to human resources data to define outcomes of interest and person-time at risk to calculate rates. Poisson and negative binomial regression with lagging were used to compare outcome rates in different windows of time surrounding the intervention. Patterns of MS injuries associated with patient-handling were contrasted to patterns of other MS injuries that would not be affected by the use of mechanical lift equipment. Results At the medical center, no change in the patient-handling MS injury rate followed the intervention. A 44% decrease was observed at the community hospital. At both hospitals, the rate of days away declined immediately — before it was reasonable for the intervention to have been adopted. Conclusions Institutional-level changes at the time of the intervention likely influenced observed results with findings only partially consistent with an intervention effect. Observational studies can be useful in assessing effectiveness of safety interventions in complex work environments. Such studies should consider the process of intervention implementation, the time needed for intervention adoption, and the dynamic nature of work environments.